2009
DOI: 10.1111/j.1468-2982.2008.01789.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Oestrogen Receptors GPR30 and ERα in Peripheral Sensitization: Relevance to Trigeminal Pain Disorders in Women

Abstract: Estrogen increases facial allodynia through its actions on activation of the MAP kinase ERK in trigeminal ganglion neurons. This goal of study was to determine which estrogen receptor is required for behavioral sensitization. Immunohistochemical studies demonstrated the presence of estrogen receptor alpha (ERα) in nuclei of larger neurons and cytoplasm of smaller neurons, and the novel estrogen receptor G-protein coupled receptor 30 (GPR30) in small diameter neurons that also contained peripherin, a marker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 51 publications
6
81
0
1
Order By: Relevance
“…In our study women are the most affected by migraine, agreeing with the literature [18,19] and a high percentage of women (40 to 50%) have migraine attacks before, during or just after menstruation, which points to an association of migraine with female hormonal levels [20]. Conversely, hormonal contraceptives may cause no change or even improve pain [21][22][23].…”
Section: /6supporting
confidence: 77%
“…In our study women are the most affected by migraine, agreeing with the literature [18,19] and a high percentage of women (40 to 50%) have migraine attacks before, during or just after menstruation, which points to an association of migraine with female hormonal levels [20]. Conversely, hormonal contraceptives may cause no change or even improve pain [21][22][23].…”
Section: /6supporting
confidence: 77%
“…Although early graphical depictions of GPER function suggested its placement in the plasma membrane at the cell surface (Filardo, 2002;Filardo et al, 2002), subsequent experimentation demonstrated that in many cell types, the majority of receptors (as determined through confocal microscopy) under steadystate conditions was localized to intracellular membranes, including the endoplasmic reticulum and Golgi apparatus (Revankar et al, 2005) with contradictory reports subsequently published Funakoshi et al, 2006;Filardo et al, 2007). Although the localization of GPER remained controversial, a majority of studies using both cellular and tissue samples yielded results consistent with a predominantly intracellular cytoplasmic membrane localization (Sakamoto et al, 2007;Albanito et al, 2008;Matsuda et al, 2008;Otto et al, 2008;Liverman et al, 2009;Terasawa et al, 2009), although nuclear localization has also been observed (Smith et al, 2009;Madeo and Maggiolini, 2010;Pupo et al, 2013). E2 is freely membrane permeable and cell surface expression is not required of an estrogen receptor, as exemplified by the predominantly nuclear localization of ERa (Hager et al, 2000).…”
Section: A Estrogensmentioning
confidence: 96%
“…GPER (mRNA and protein) is expressed throughout the central and peripheral nervous system (although not universally) of both female and male rodents, including the cortex, hippocampus, hypothalamus, specific nuclei of the midbrain, the trigeminal nuclei and cerebellum Purkinje layer of the hindbrain, the anterior, intermediate and neural lobes of the pituitary, as well as the spinal cord and dorsal root ganglia (Brailoiu et al, 2007;Dun et al, 2009;Hazell et al, 2009). The activation of ERK1/2 in trigeminal ganglion neurons and the increased allodynia induced by PPT [4,49,-pyrazole-1,3,5-triyl) trisphenol] and G-1 has led to the conclusion of roles for both ERa and GPER in peripheral sensitization (Liverman et al, 2009); however, with the recent demonstration that PPT can also function as a GPER agonist (Petrie et al, 2013), it is possible that both responses, in fact, were mediated by GPER, because independent methods to assess receptor involvement were not employed. G-1 also depolarizes spinal cord neurons , stimulates mechanical hyperalgesia via protein kinase C« activation (Kuhn et al, 2008), and mediates visceral hypersensitivity in the absence of inflammation (Lu et al, 2009).…”
Section: Nervous Systemmentioning
confidence: 99%
“…Nonetheless, part of this difference may be justified by the fact that when TMD and migraine co-occur, migraine tends to be more severe than when they do not, which would channel women with more severe TMD to the headache center rather to the TMD center 10 . Furthermore, it is well established that women are more likely than men to suffer pain episodes as a function of neuroendocrine events and of the reproductive stage 10,[24][25][26] . Menstrual migraine is well known to be more severe and refractory to treatment than non-menstrual migraine 10,24 , and a limitation of our study was not to characterize this migraine subgroup, since this would require longitudinal follow-up and use of dairies.…”
Section: Discussionmentioning
confidence: 99%